PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA SEKOLAH MADRASAH IBTIDAIYAH (MI) PLUS FATAHILLAH CILEDUG KOTA TANGERANG - Tukidi; Oktaviani, Selly Amanda; hastuti, wedia; Ida Adhani (Jurnal Nusa Manajemen, 2025)
This study involved 44 employees at MI Plus Fatahillah Ciledug, Tangerang City, and employed a quantitative approach using multiple linear regression analysis, the coefficient of determination test (R²), partial test (t), and simultaneous test (F) with SPSS version 25. The analysis resulted in the regression equation Y = 3.299 + 0.297X1 + 0.326X2 + 0.339X3. The Adjusted R² value of 0.714 indicates that 71.4% of employee performance is explained by leadership style, compensation, and work environment, while the remaining 28.6% is influenced by other factors. The t-test results show that all three variables have a significant partial effect on employee performance, with significance values below 0.05. Leadership style, compensation, and work environment each have a positive effect. The F-test shows an F count of 36.751 > F table of 2.84 with a significance of 0.000, indicating that the three variables simultaneously have a significant effect on employee performance.